Relationship between release of ?-endorphin, cortisol, and trauma severity in children with blunt torso and extremity trauma - Okur, Hamit; Kucukaydin, Mustafa; Ozokutan, Bulent Hayri; Muhtaroglu, Sabahattin; Kazez, Ahmet; Turan, Cuneyt (Lippincott Williams & Wilkins, 2007)
Purpose: To determine the levels of beta-endorphin and cortisol in children with multiple injuries and to determine whether there is any difference between and compare the severity of trauma and beta-endorphin and cortisol release as calculated using Pediatric Trauma Score (PTS). Methods: During a 10-month period, 80 children with multiple injuries admitted to a University Hospital's Pediatric Surgery Department were studied. Blood samples were obtained immediately at admission and a PTS of each patient was calculated. The correlation between PTS and hormonal values were searched. The children were classified into two groups according to their PTS. Group 1 had PTS > 8 and group 2 had PTS <= 8. The two groups were also compared with respect to their beta-endorphin and cortisol values. Results: There was a linear correlation between beta-endorphin and cortisol values and the injury severity. The levels were higher in the patients with more severe injuries. There were 60 patients in group 1 and 20 patients in group 2. Their ages were 9.2 +/- 4.1 and 9.7 +/- 4.2 years, respectively (p > 0.05). The mean PTS for group 1 patients was 11 +/- 0.8 and for group 2 patients was 7.4 +/- 1.2 (p < 0.001). The mean plasma 13-endorphin concentrations were 124.4 +/- 114.4 pg/mL in group 1 patients and 261.6 +/- 231.2 pg/mL in group 2 (p < 0.001). The respective plasma cortisol concentrations in the two groups were 22.5 +/- 10.3 mu g/dL and 30.8 +/- 17.2 mu g/dL (p < 0.05), respectively. Conclusions: The results of this study show that the plasma beta-endorphin and cortisol levels are elevated in children after blunt trauma and the degree of elevation is related to the injury severity.
Keywords: trauma; pediatric; stress response; endorphin; cortisol